Meta-Analysis of Sociological Factors Effective to Social Development with Emphasis on the Role of Urban and Rural Origin in Iran - mohammad reza Hosseini (توسعه اجتماعی)
The purpose of this study is to meta-analyze Sociological factors.In order to conduct this research,18 related studies that were conducted during the years 2007-2018 and with the aim of investigating the relationship between social factors and social development and were published in scientific-research journals, were selected. Selected surveys have been conducted by survey method and using survey tools in different statistical communities and based on reliable metrics.In the first step, the assumptions of homogeneity and publication error were examined.Findings indicated heterogeneity of effect size and lack of publication bias in the studied studies.In the second stage, the effect size coefficient and the moderating role of the social origin variable were evaluated using the second version of CMA software.The results showed that the magnitude of the effect or coefficient of influence of social factors on social development is equal to 0.451, which according to Cohen's interpretive system, this amount is considered as an average upward effect. Also, considering social origin as a moderating variable, this coefficient is for those whose social origin is urban.The size of the effect in the random model is 0.419 and those whose social origin is rural, the size of the random effect is equal to 0.524, both social origins are significant at the level of 0.001 therefore, according to the size of the effect obtained for each of the geographical areas under discussion,it can be concluded that the impact of social factors in rural areas has been more effective. Also, in general, the size of the work in both social origins is 0.446.